Complications of peripherally inserted central venous catheters in neonates: Lesson learned over 2 years in a tertiary care centre in India - Amit Singh; Minu Bajpai; Shasanka Shekhar Panda; Manisha Jana (Wolters Kluwer Medknow Publications, 2014)
Background: The objective of this study was to assess the complications of peripherally inserted central venous catheters (PICC) in neonates admitted to neonatal surgical intensive care unit (NSICU). Patients and Methods: Retrospective analysis of 237 neonates admitted to NSICU from January 2010 to December 2011 was done. Results: Mean age at presentation was 5.8 days and mean weight was 1.94 kg. Mean number of attempts was 1.14, mean duration of insertion 8.4 min and mean duration of patency of catheter 3.14 days. Most common site of catheter insertion was upper extremity (basilic followed by cephalic). Overall complications were seen in 47 (23%) cases. Infectious complications were seen in 22 (10.7%) and non-infectious in 25 (12.2%) cases. Significant correlation existed between non-infective complications and insertion site (P = 0.03) and duration of PICC (P = 0.04). Conclusion: Precautions should be taken and position must be confirmed during and after PICC insertion to avoid undue complications.